2018
DOI: 10.1002/cvj.12073
|View full text |Cite
|
Sign up to set email alerts
|

Religious Commitment's Moderating Effect on Refugee Trauma and Growth

Abstract: The authors assessed religious commitment's moderating effect on the relationship between posttraumatic stress disorder and posttraumatic growth (PTG) in adult Liberian refugees who experienced trauma from war (N = 444). Results indicated that religious commitment predicted PTG and had an interaction effect on the relationship between trauma and PTG, albeit a negative one. Counselors should therefore gauge clients’ worldviews in terms of religion or spirituality before integrating spiritual or religious issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
2
14
1
Order By: Relevance
“…Additionally, hope and social support play buffering role and can affect individual's capacity to move towards growth even in the presence of stress these results are consistent with previous literature. 17,[20][21][22] Conclusions: In the present study results confirmed that social support and hope play protective role in aftermath of war trauma.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, hope and social support play buffering role and can affect individual's capacity to move towards growth even in the presence of stress these results are consistent with previous literature. 17,[20][21][22] Conclusions: In the present study results confirmed that social support and hope play protective role in aftermath of war trauma.…”
Section: Discussionsupporting
confidence: 82%
“…Strong ideological commitment and religious beliefs have been identified as particularly adaptive coping resources that were connected to the psychosocial well-being of refugee youth in several other studies (e.g., Acquaye et al, 2018;McMichael et al, 2011;Weine et al, 2014). Religion and spirituality, commonly reported in resilience and posttraumatic growth case reports, may afford protection through building hope and providing a sense that life has meaning (Masten, 2014).…”
Section: Adaptive Coping Strategiesmentioning
confidence: 97%
“…Based on the assumption that medical and psychosocial care focuses mainly on the so-called ‘primary needs’ while neglecting the other needs, we focused on spiritual needs to meet refugees’ more comprehensive requirements. These so-called ‘secondary needs’ could be an important resource to cope with the new life situation in a foreign country and culture, as they utilize more complex resources to cope with the difficult situation [ 21 , 31 , 32 ]. Such a resource-oriented perspective seems to be even more relevant in the case of negative and/or dysfunctional appraisals of the new post-migration life situation.…”
Section: Introductionmentioning
confidence: 99%